Fetal cardiac tumor: echocardiography, clinical outcome and genetic analysis in 53 cases. (12th June 2019) - Chen, J.; Wang, J.; Sun, H.; Gu, X.; Hao, X.; Fu, Y.; Zhang, Y.; Liu, X.; Zhang, H.; Han, L.; He, Y.
ABSTRACT: Objective: To analyze the imaging and clinical features of fetal cardiac tumors, and to explore the relationship between tuberous sclerosis complex (TSC) and cardiac rhabdomyoma in the fetus. Methods: Fifty‐three women pregnant with a fetus affected by cardiac tumor(s) were examined by standardized fetal echocardiography (FE), and fetuses, mothers and fathers, including other relevant family members if necessary, underwent familial TSC genetic testing. Relevant pathological features, including pathological findings at clinical examination of liveborn infants and autopsy findings in terminated cases, were noted. Results: Of the 53 fetuses, 37 had multiple cardiac tumors and 16 had a single cardiac tumor detected by FE. In all 53 fetuses and their families, TSC genetic testing was successful, showing that 37 of the fetuses had a TSC1 ( n = 6) or TSC2 ( n = 31) pathogenic or suspected pathogenic mutation, of which 25 were spontaneous and 12 were familial mutations. The proportion of single and multiple cardiac tumors at FE was significantly different between the group of fetuses with positive genetic test results and that with negative results for TSC (31% and 86%, respectively), although the presence of multiple or single tumors was not associated with the type of TSC mutation. The decision to terminate the pregnancy was made by 45 women and their families, and eight fetuses were liveborn. Autopsy was performed in 38 fetuses, which revealed 36 cases with pathologically confirmed cardiac rhabdomyoma, one case of hemangioma and one case of fibroma. 93% of fetuses with multiple rhabdomyomas at autopsy and 71% of those with a single cardiac rhabdomyoma harbored a TSC1 or TSC2 mutation. Conclusion: Cardiac rhabdomyoma is the most common cardiac tumor in the fetus. The correlation between cardiac rhabdomyoma and TSC is strong regardless of the presence of single or multiple tumors. For fetuses with suspected cardiac rhabdomyoma identified by FE, prenatal genetic testing for TSC of both fetus and family members is recommended. A positive genetic diagnosis can help in counseling and planning for neonatal treatment. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.